Recent Study among Medical College Students to Find Out Association of Stress, Loneliness & Depression with Existing Relationship with Their Mother - Vijay, Chouhan; Madhur, Thakur; Vipin, Thakur; Sukh Dayal, Kumhar (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Aim: The purpose of this study is to compare the level of warmth, autonomy and hovering in mother with level of stress loneliness and depression with respect to student. Background: Emerging adulthood is defined by efforts to develop one's individuality in areas such as love, work, and worldview. Work is regarded as preparation for a later adult career during emerging adulthoods. This is the time when the groundwork is laid for the jobs and careers that will be pursued later in life. With higher level of freedom and greater time spent in exploration of possible career paths, jobs with short term commitments. Methods: A cross-sectional study of 150 medical college students at MGM Medical College in Indore was conducted to determine the existing relationship between medical students and their mothers. The information was gathered using a pre-designed semi-structured questionnaire with 16 questions. Result: The Pearson co-relation test reveals a significant relationship between mother warmth and stress, loneliness, and depression. With increase in warmth there is decrease in, loneliness and depression. Conclusion: When mothers are warmer/affectionate to their children, they feel more secure and able to communicate better with their mother, which develops a habit in them that helps them communicate better with others as well. Mother's autonomy has a positive relationship with stress, loneliness, and depression. When a mother gains more autonomy over her three children, the level of stress, loneliness and depression rises.